Pengembangan Buku Petunjuk Praktikum Lapangan Berbasis Jigsaw Sebagai Sumber Belajar Identifikasi Vertebrata - Nasrianty, Nasrianty; Pratomo, Ryan Humardani Syam (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
This research aimed to evaluate the validity and feasibility of the Jigsaw-based field practicum guidebook as a learning resource for vertebrate identification. The development of the guidebook followed the Borg and Gall model for research-based product development. The research stages included a preliminary study and a field trial process. Based on assessments from two validators, the guidebook received an average score of 4.68, which falls within the